2011
DOI: 10.1111/j.1540-5826.2011.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Reading Science Text: Challenges for Students with Learning Disabilities and Considerations for Teachers

Abstract: In science classes, teachers must consider the need for explicit, systematic reading instruction for students with learning disabilities (LD) while navigating the constructivist and activity‐oriented methods typically employed in science instruction. The complexity of scientific information conveyed through print may make reading science texts the greatest challenge that students with LD encounter in school. Fortunately, researchers have established that, by fostering students’ prior knowledge, providing text … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 65 publications
(160 reference statements)
1
46
0
2
Order By: Relevance
“…Among these studies, mnemonic illustrations , graphic organizers (Darch & Eaves, 1986;Griffin et al, 1991), and semantic feature analyses (Bos & Anders, 1990) indicated high effects for increasing reading comprehension in science. Mason and Hedin (2011) updated the expository text synthesis conducted by Gajria and colleagues (2007) by exploring effective content enhancements and cognitive strategies for teaching reading comprehension of science text. Mason and Hedin (2011) updated the expository text synthesis conducted by Gajria and colleagues (2007) by exploring effective content enhancements and cognitive strategies for teaching reading comprehension of science text.…”
Section: Science Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these studies, mnemonic illustrations , graphic organizers (Darch & Eaves, 1986;Griffin et al, 1991), and semantic feature analyses (Bos & Anders, 1990) indicated high effects for increasing reading comprehension in science. Mason and Hedin (2011) updated the expository text synthesis conducted by Gajria and colleagues (2007) by exploring effective content enhancements and cognitive strategies for teaching reading comprehension of science text. Mason and Hedin (2011) updated the expository text synthesis conducted by Gajria and colleagues (2007) by exploring effective content enhancements and cognitive strategies for teaching reading comprehension of science text.…”
Section: Science Textmentioning
confidence: 99%
“…Unfortunately, given the small number of studies within each intervention sub-category, no conclusive results could be drawn regarding overall effectiveness of the individual content enhancement approaches. Unlike the Gajria et al (2007) synthesis, Mason and Hedin (2011) did not include overall effect sizes in their review. In their review, they identified studies that fostered prior knowledge of science content, included text enhancements, or used strategy instruction during science reading for students with LD.…”
Section: Science Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the somewhat inherent complexity of STEM coursework, students with SLD need (and are entitled to) specially designed instructional supports intended to help bridge any gaps between their overall cognitive processing struggles and the demands of the curriculum (Hallahan, Lloyd, Kauffman, Weiss, & Martinez, 2005), which includes the ability to read and comprehend complex texts (Mason & Hedin, 2011). Specially designed supports in STEM classrooms can include applications of assistive or instructional technology, in addition to more traditional approaches to teaching and learning (e.g., explicit and direct instruction; Kennedy, 2011).…”
Section: Mismatch 2: Content Demands That Overwhelm Student Cognitionmentioning
confidence: 99%
“…These intertwined challenges can restrict learning and overall achievement (Deshler & Shumaker, 2006). Such complex challenges are prevalent in science, technology, engineering, and math (STEM) coursework, given the hefty demands of vocabulary terms and concepts (Therrien, Taylor, Hosp, Kaldenberg, & Gorsh, 2011), obtuse expository texts (Mason & Hedin, 2011), and subjectspecific problems that need to be addressed through inquiry and other advanced cognitive processes (Lee & Spratley, 2010).…”
mentioning
confidence: 99%